MORALITAS QUR’ANI PERSPEKTIF FAZLUR RAHMAN - Moh. Alwy Amru Ghozali (Proceeding of Conference on Strengthening Islamic Studies in The Digital Era, 2021)
Modernity is not a small impact to human life. Along with advances in technology and science, the life that completely materialist and pragmatic increasingly is uncontrollable. For Muslims, returning to teaching of the al-Qur’an is a necessity. In this case, Fazlur Rahman understands that morality is the principle teaching of the various thematic narrative of the al-Qur’an, whether Divine, human freedom, nature, demons, and eschatology. By descriptive-analytical approach, the author captures that concept of morality Fazlur Rahman can be used to answer problem of the modernity. Keywords: modernitas, Fazlur Rahman, moralitas, double movement